The Motivation and Transformation of White Culturally Responsive Higher Education Professors - China Carter Jenkins (Adult Education Research Conference, 2013)
The purpose of this round table is to discuss the motivation, transformation and pedagogy of eight White culturally responsive professors featured in the author’s dissertation. This dialogue will highlight the participants’ perspectives on culturally relevant pedagogy (CRP) and compare it with the discourse of CRP in higher education.